2017
DOI: 10.1177/1075547016688324
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Nature-Based Citizen Science in Promoting Individual and Collective Climate Change Action? A Systematic Review of Learning Outcomes

Abstract: As a model of communication and engagement, citizen science has the potential to promote individual and collective climate change action. This article systematically reviewed literature that jointly addressed climate change and nature-based citizen science and identified 23 reported learning outcomes. Overall, evidence related to learning outcomes was limited across reviewed studies, but documentation of outcomes that are directly relevant to collective climate action was particularly scarce. Findings suggest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(84 citation statements)
references
References 70 publications
2
77
0
Order By: Relevance
“…Maintaining the engagement and enthusiasm of volunteer recorders around the world is crucial: not only do national and international initiatives like the Global Biodiversity Information Facility (GBIF) fuel a demand for biodiversity data, but (as noted in the next section) involvement of volunteers in biodiversity-related citizen science is linked to a diverse range of benefits for participants. These may include cognitive and experiential learning outcomes and a strengthened connection with nature (Groulx et al 2017) and mental and physiological health benefits associated with nature engagement (Russell et al 2013). Biodiversity-related citizen science may thus not only contribute to biodiversity conservation through direct provision of data, but also indirectly through strengthening participants' awareness of and connection with biodiversity and the natural world.…”
Section: Introduction: a Different Perspective On Citizen Scientistsmentioning
confidence: 99%
“…Maintaining the engagement and enthusiasm of volunteer recorders around the world is crucial: not only do national and international initiatives like the Global Biodiversity Information Facility (GBIF) fuel a demand for biodiversity data, but (as noted in the next section) involvement of volunteers in biodiversity-related citizen science is linked to a diverse range of benefits for participants. These may include cognitive and experiential learning outcomes and a strengthened connection with nature (Groulx et al 2017) and mental and physiological health benefits associated with nature engagement (Russell et al 2013). Biodiversity-related citizen science may thus not only contribute to biodiversity conservation through direct provision of data, but also indirectly through strengthening participants' awareness of and connection with biodiversity and the natural world.…”
Section: Introduction: a Different Perspective On Citizen Scientistsmentioning
confidence: 99%
“…The process of earning social licence is similar to citizen science because it brings members of the public together to discuss and address issues of common concern. The opinions of the coordinators agree with reflections in the literature on the need to properly understand the potential of citizen science as a communication and engagement tool (Groulx et al 2017).…”
Section: Resultsmentioning
confidence: 54%
“…A metaanalysis of learning effects showed that gaining content knowledge -reflecting the topic of focus -was by far the most reported type of learning in citizen science projects ( Stepenuck and Green 2015). Another meta-analysis on climate change and citizen science showed the outcome of new knowledge being the most important impact of citizen science in climate change (Groulx et al 2017). In contrast, according to this analysis, relatively few studies refer to outcomes beyond new knowledge gains, like a sense of empowerment, a feeling of contributing to science, or insight into one's values and interests (Groulx et al 2017).…”
Section: Understanding the Impact Of Citizen Science Projects In Envimentioning
confidence: 99%
“…Another meta-analysis on climate change and citizen science showed the outcome of new knowledge being the most important impact of citizen science in climate change (Groulx et al 2017). In contrast, according to this analysis, relatively few studies refer to outcomes beyond new knowledge gains, like a sense of empowerment, a feeling of contributing to science, or insight into one's values and interests (Groulx et al 2017). The authors state that these results might be due partly to a notable gap in documented evidence.…”
Section: Understanding the Impact Of Citizen Science Projects In Envimentioning
confidence: 99%
See 1 more Smart Citation